2022
DOI: 10.1039/d2ob00682k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4-(organoselenyl) oxazolones via cyclization of N-alkynyl ethylcarbamates promoted by organoselenium

Abstract: The organoselenyl iodide promoted the intramolecular nucleophilic cyclization of N-alkynyl ethylcarbamates in the synthesis of 4-(organoselenyl) oxazolones. The reaction was regioselective giving the five-membered oxazolone products as the unique regioisomer...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Alternatively, the oxazolones 89 were also prepared by a direct cyclization involving ynamides and an electrophilic species of organoselenium under transition-metal-free conditions. [132] Diorganoyl diselenides were efficiently applied to the intramolecular cyclization of alkynyl tosylhydrazones in the synthesis of organoselenyl pyrazoles 91 (Scheme 86). [133] The results of the reaction conditions optimization showed that the use of diorganyl diselenides (2.0 equiv) and iron(III) chloride (2.0 equiv) in the presence of dichloroethane, at room temperature delivered the products in good yields.…”
Section: Organoseleno Cyclization Of Alkynesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the oxazolones 89 were also prepared by a direct cyclization involving ynamides and an electrophilic species of organoselenium under transition-metal-free conditions. [132] Diorganoyl diselenides were efficiently applied to the intramolecular cyclization of alkynyl tosylhydrazones in the synthesis of organoselenyl pyrazoles 91 (Scheme 86). [133] The results of the reaction conditions optimization showed that the use of diorganyl diselenides (2.0 equiv) and iron(III) chloride (2.0 equiv) in the presence of dichloroethane, at room temperature delivered the products in good yields.…”
Section: Organoseleno Cyclization Of Alkynesmentioning
confidence: 99%
“…Ts−N and Ms−N in the alkynes led to the stereoselective reduction of the carbon‐carbon triple bond to give the corresponding vinyl selenides 90 without the cyclized product 89 (Scheme 85). Alternatively, the oxazolones 89 were also prepared by a direct cyclization involving ynamides and an electrophilic species of organoselenium under transition‐metal‐free conditions [132] …”
Section: Diorganyl Diselenides Promoting Cyclization Reactionsmentioning
confidence: 99%